The Association of Serum Anti-Lysosomal-Associated Membrane Protein-2 Antibody with Vasculitis Combined with Hypertension - Bin Zhu; Xintian Cai; Qing Zhu; Ting Wu; Shasha Liu; Shanshan Liu; Jing Hong; Nanfang Li (International Journal of Hypertension)
The aim of this study was to explore the association of serum anti-lysosomal-associated membrane protein-2 (anti-LAMP-2) antibody with vasculitis combined with hypertension (VAS-HTN). A total of 51 VAS-HTN patients, 46 essential hypertension (EH) patients, and 46 healthy controls (HC) were included in the study. Serum anti-LAMP-2 antibody levels are increased in VAS-HTN patients as compared with EH and HC (all P<0.05). Serum anti-LAMP-2 antibody levels were significantly higher in active stage patients than those in non-active stage patients and HC (all P<0.05). The correlation analysis showed a significant positive correlation between serum anti-LAMP-2 antibody levels and the Birmingham Vasculitis Activity Score (BVAS) and hypersensitive C-reactive protein (Hs-CRP) (all P<0.05). Among the subsets of VAS-HTN, the levels of serum anti-LAMP-2 antibody were remarkably higher in all VAS-HTN subsets compared with HC (all P<0.05). More interestingly, the levels of serum anti-LAMP-2 antibody were remarkably increased in polyarteritis nodosa (PAN) patients compared with ANCA-associated vasculitis and Takayasu arteritis patients (all P<0.05). In addition, there was a significant positive correlation between serum anti-LAMP-2 antibody levels and BAVS and Hs-CRP in PAN patients (all P<0.05). Multivariate logistic regression analysis showed that the anti-LAMP-2 antibody was independently associated with VAS-HTN. The levels of serum anti-LAMP-2 antibody were remarkably increased in VAS-HTN patients compared to EH and HC and might reflect the disease activity. The anti-LAMP-2 antibody may be a potential biomarker for diagnosis and estimating the disease activity in VAS-HTN.